IMPORTANCE OF CORPORATE CULTURE - Bortesi Longhi, Luis (2011)
The corporate culture has two addresses, one pointing outward to the social, community and indirectly also the whole country by the company contribution to employment and national development. Corporate culture also comprises an important and primary environmental care and all that joint described above reflects the general title of “Social Responsibility”. The other direction is toward the inside of the organization and in this sense refers to maintaining harmony and solidarity as company values that are a powerful Intangible Assets. It is remarkable that have become increasingly important intangible assets in the past were limited to trademarks and patents but now have spread to other values fundamental importance subtle to the point that sometimes constitute the largest item of heritage business. In this article we will particularly discuss in detail the factors considered remarkable in terms of corporate culture within the organization.